2009
DOI: 10.1111/j.1365-2222.2009.03333.x
|View full text |Cite
|
Sign up to set email alerts
|

Digested Ara h 1 has sensitizing capacity in Brown Norway rats

Abstract: From this study, it can be concluded that lability of a food allergen to gastrointestinal digestion does not necessarily abrogate its allergenic sensitizing potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
77
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(82 citation statements)
references
References 49 publications
4
77
1
Order By: Relevance
“…Gastric digestion was performed essentially as described by Bøgh et al 10 In short, pepsin immobilized to agarose (P0609, Sigma, St. Louis, MO) was washed two times (100g, 1 min) in 10 mL of 1 mM HCl. Purified Ara h 1 (2.4 mg/mL in 150 mM NaCl) was adjusted to pH 2.5 with 1 M HCl and added to the immobilized pepsin to yield an activity of pepsin of approximately 170 U per mg Ara h 1.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Gastric digestion was performed essentially as described by Bøgh et al 10 In short, pepsin immobilized to agarose (P0609, Sigma, St. Louis, MO) was washed two times (100g, 1 min) in 10 mL of 1 mM HCl. Purified Ara h 1 (2.4 mg/mL in 150 mM NaCl) was adjusted to pH 2.5 with 1 M HCl and added to the immobilized pepsin to yield an activity of pepsin of approximately 170 U per mg Ara h 1.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…23,24 Ara h 1 is a readily digestible allergen, being digested to small peptide fragments by gastroduodenal digestion. 9,10 Even though Ara h 1 is a labile protein, Eiwegger et al 9 and Bøgh et al 10 showed that the digestion products of Ara h 1 retain allergenic potential, being able to sensitize as well as elicit allergic reactions. These studies indicated that aggregation of peptides may play a major role in maintaining allergenic activity.…”
Section: ■ Introductionmentioning
confidence: 99%
See 3 more Smart Citations